(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2022)
The article defends the deliberative model of democracy against the traditional competitive liberal model. An attempt was made to approach the majority rule in Aristotle’s Politics, identified with the democratic regime and the constitutional regime (politeia). The experimental mark (perspective defended in this article) of political regimes in Politics was taken into account, an idea of ​​unfinished institutions and constantly subject to debate (experimentalism). In this sense, a theoretical space compatible with the public debate on institutions is democratic experimentalism, a theoretical movement that proposes a central idea of ​​innovation and institutional rearrangements, within which is the deliberative model of democracy, as a basis for political legitimacy.